2022
DOI: 10.31004/basicedu.v6i4.3116
|View full text |Cite
|
Sign up to set email alerts
|

Mengembangkan Motivasi Belajar Siswa melalui Strategi Pembelajaran Berdiferensiasi: Sebuah Kajian Pembelajaran dalam Perspektif Pedagogik-Filosofis

Abstract: Kemajuan teknologi yang semakin pesat diiringi perkembangan dunia yang semakin maju menuntut insan manusia mampu beradaptasi dengan segala perubahan yang terjadi dan salah satunya mempengaruhi dunia pendidikan. Belajar tidak hanya diperoleh dalam satu waktu melainkan melalui berbagai cara dengan mengoptimalkan segala pancaindera yang dimiliki setiap manusia itu. Tujuan penelitian ini sebagai cara untuk mempersiapkan peserta didik yang dapat belajar dalam segala situasi sehingga perlu dilatih sejak dini bagaima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 11 publications
(11 reference statements)
0
16
0
9
Order By: Relevance
“…From the description above, it can be concluded that the results of implementing differentiated learning through play activities in early childhood through play have succeeded in facilitating the development of cognitive, affective, and psychometric aspects of early childhood optimally (Handiyani & Muhtar, 2022). The results achieved from the implementation of differentiated learning through play activities are in accordance with the program objectives, both in the form of general goals and special objectives.…”
Section: Implementation Of Differentiated Learning Through Playing Ac...mentioning
confidence: 78%
See 1 more Smart Citation
“…From the description above, it can be concluded that the results of implementing differentiated learning through play activities in early childhood through play have succeeded in facilitating the development of cognitive, affective, and psychometric aspects of early childhood optimally (Handiyani & Muhtar, 2022). The results achieved from the implementation of differentiated learning through play activities are in accordance with the program objectives, both in the form of general goals and special objectives.…”
Section: Implementation Of Differentiated Learning Through Playing Ac...mentioning
confidence: 78%
“…The characteristics or characteristics of differentiated learning include (Faiz et al, 2022); the learning environment invites students to learn, the curriculum has clearly defined learning objectives, there is an ongoing assessment, teachers respond to or respond to student learning needs, and effective classroom management (Handiyani & Muhtar, 2022). Examples of classes that apply differentiated learning are when the teacher's learning process uses various ways so that students can exploit the curriculum content, the teacher also provides a variety of activities that make sense so that students can understand and have information or ideas, and the teacher provides a variety of options where students can demonstrate what they learn (Lestariningrum, 2022).…”
Section: Introduction *mentioning
confidence: 99%
“…The relationship between teachers and students becomes stronger and stronger with this differentiated learning, so that students become enthusiastic about learning. Apart from that, being able to differentiate learning helps students to be more confident and independent and explore students' potential and abilities (Marlina, 2019;Handiyani, & Muhtar, 2022;Kamalia, 2023).…”
Section: Figure 3 Elements Learningmentioning
confidence: 99%
“…Diantara upaya agar tercapainya tujuan pembelajaran yaitu mengerti akan bagaimana siswa belajar dan bagaimana keberhasilan guru dalam proses mengajarkan peserta didiknya. Handiyani, (2022) menejelaskan proses pendidikan harus diorientasikan pada upaya dalam mengembangkan potensi peserta didik sebagai individu yang memiliki karakteristik perbedaaan unik antara satu dengan lainnya. Maka itu pembelajaran mempunyai komitmen untuk melahirkan potensi usaha manusia yang bernilai dan memyiapakn peserta didik untuk menjadi harapan untuk masa depan yang berkompeten, memiliki kemandirian, berfikir kritis dan memiliki kreativitas dan bisa menangani masalah yang timbul.…”
Section: Pendahuluanunclassified